Innovative Strategies to Promote Literacy Skills in Pakistan (British Journal of Multidisciplinary and Advanced Studies, 2024)
Empowering students with literacy skills so that they can grow and compete in the global workforce can be achieved via a strong and robust educational system. However, in some third world countries including Pakistan, ready access to schools may not be a viable option for some students due to resource constraints or due to cultural or religious limitations. Innovative strategies to enhance literacy skills can have a significant impact in alleviating gaps between those students who are denied educational opportunities vis-à-vis privileged students who receive quality education, and several non-governmental organizations (NGOs) have taken creative steps to provide opportunities for children in remote parts of Pakistan to develop literacy skills and promote a reading culture. This paper will explore the results from a qualitative study on three NGOs and explain how they promote literacy for the most vulnerable populations.